2022
DOI: 10.21123/bsj.2022.19.4.0716
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective and Immuno-supportive Role of Alcea kurdica against Stress Induced Lesion in Japanese Quails

Abstract: The conducted research was done in Grda rasha field (Salahaddin University) for one month to compare the impacts of Alcea kurdica powder, Rifaxmine, and Ranitidine as anti-lesion and immune-strengthening agents on stress-induced quails which are affecting their growth rate and in severe cases causing gizzard erosion and deep intestinal lesions. To do that, 75 quails (12 weeks old) were grouped into six treatments with different additives. (T0-) = Negative control (Stress-induced Without treatment), (T0+) = Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…55 IBD is a digestive tract disease that mainly affects the large intestine and can be originated from genetic and oxidative stress (key pathophysiological) risk factors. 45 IBD primarily includes Crohn's disease and ulcerative colitis, which are similar in terms of originating from immunologic overreaction and different from each other based on their involvement in the digestive system. 56 Moreover, oxidative stress studies have shown the transformation of sensory cells into neoplastic cells in many IBD cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 IBD is a digestive tract disease that mainly affects the large intestine and can be originated from genetic and oxidative stress (key pathophysiological) risk factors. 45 IBD primarily includes Crohn's disease and ulcerative colitis, which are similar in terms of originating from immunologic overreaction and different from each other based on their involvement in the digestive system. 56 Moreover, oxidative stress studies have shown the transformation of sensory cells into neoplastic cells in many IBD cases.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was moved into separate tubes and investigated for the antioxidant enzymes (CAT, SOD and GPX) and MDA content (kits from Elabscience, USA). 45 …”
Section: Methodsmentioning
confidence: 99%
“…et al Flavonoids protect the gastric mucosa from damage by increasing the mucosal prostaglandin content and by inhibiting histamine secretion. Phenolics and terpenoids have played a substantial role in the development of human medicine as antioxidants, and through their free radical scavenging, and gastroprotective actions (Enin ., et al 2021b;Jabbar, 2022;Li ., 2022). In this study, we et al summarized therefore, that these chemical compounds which are found to be present in this extract and fractions may be responsible for the observed antiulcerogenic activities…”
Section: Administration Of the Fractions Of Extract Andmentioning
confidence: 97%
“…antioxidant 4,14,17,32 . The phenolic compounds are also linked with improving defense mechanisms through reversing ROS formation, increasing cell survival, and decreasing nuclear damages and microorganism attacks [38][39][40][41] .…”
Section: Chemical Profilementioning
confidence: 99%